Pelatihan Cara Berpikir Simbolik-Matematik di SMA BOPKRI 2 Yogyakarta - Santosa, Raden Gunawan; Tampubolon, Junius Karel (Universitas Pendidikan Ganesha, 2020)
Symbolic-Mathematical Thinking is a technique of thinking to solve mathematical problems. This technique is the result of a combination of Symbolic Logic and Mathematics. In general there are three symbolic logic activities that are applied to Mathematics, namely reading symbols, logical equivalents and logical implications. This Pengabdian kepada Masyarakat (PkM) has activities to train Symbolic-Mathematical thinking using 15 strategies for BOPKRI 2 high school students. The results of this training are three important things. The first result is the type of problem that is most difficult for students to face is the type of problem that requires drawing conclusions that refer to standard mathematical definitions. The second thing is for the type of use of model settlement strategies in a system and the type of seeing patterns, students tend to be able to solve problems after being given instructions on how the model fits the problem and the pattern the problem has. Whereas the third is from two groups of students the class turns out that the continuous class attending the training gets more symbolic-mathematical thinking skills improvement than the other classes.